Transcripts of "Tanzania and Kenya, Swahili program series, 1966-1970" - Nganda, Ben; Pieterse, Cosmo, 1930-; Duerden, Dennis ([Dennis Duerden collection of sound recordings relating to African novelists, poets, playwrights, artists and musicians; African history, politics, and social questions], 2012)
This collection contains plays, (including Cosmo Pieterse's "Paukwa") short stories, by Nganda, hamisis, and oral traditions, as well as discussion on the following topics: "Inside an African Government;" nations and leaders; religion; paying for government; "Swahili; Africa and the World;" travellers in Africa; cities; need for law; human rights; diplomacy -- "His Excellency the Ambassador;" journalism; change and control; faces of freedom; man and space; and migration.